(3ShGWY GdCfhGQ aj UMjM GdSff hGdBKGQs
(3ChdgG (B:s
(3jHJOF HeSfO YHO Gddg Hf YeQ Hf GdNWGH s
(3BNQgG (B:s
(3hjfJgi HGdMOjK GdJGSY hGdKeGfjf HYO GdeGFI ajeG QhGg GdHNGQi hGfaQO Hg ai UMjMg Yf CHj gQjQI ef eSfOg s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B82 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdCRgQ (B((3MOjK (B(292) 2140) s
Keywords: (3GdMOjK h GdeUWdMs